2010
DOI: 10.1007/s12640-010-9204-0
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Pyrithiamine Increases β-Amyloid Accumulation, Tau Hyperphosphorylation, and Glycogen Synthase Kinase-3 Activity in the Brain

Abstract: Decreased thiamine-dependent enzyme activity and/or thiamine deficiency (TD) have been linked to Alzheimer's disease (AD). In this study, we administered pyrithiamine, an anti-thiamine compound, to both APP/PS1 transgenic mice and wild-type littermate control mice; alternatively, we induced TD by thiamine-depleted diet. Pyrithiamine treatment and diet-induced TD impaired the memory of wild-type mice, but had little effect on APP/PS1 mice. Pathophysiologically, pyrithiamine treatment and diet-induced TD aggrava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 55 publications
2
24
0
Order By: Relevance
“…We further tested these effects using a complementary pharmacological approach, by treating neurons with pyrithiamine, a competitive substrate for Tpk1 that can be phosphorylated to form pyrithiamine diphosphate 18 but cannot functionally substitute for TDP. Pyrithiamine treatment has been shown to induce symptoms similar to those of thiamine deficiency in animals 19 . Neurons were transfected with GFP on DIV 6, and treated with pyrithiamine (50 μM) from DIV 7 to DIV 9.…”
Section: Resultsmentioning
confidence: 99%
“…We further tested these effects using a complementary pharmacological approach, by treating neurons with pyrithiamine, a competitive substrate for Tpk1 that can be phosphorylated to form pyrithiamine diphosphate 18 but cannot functionally substitute for TDP. Pyrithiamine treatment has been shown to induce symptoms similar to those of thiamine deficiency in animals 19 . Neurons were transfected with GFP on DIV 6, and treated with pyrithiamine (50 μM) from DIV 7 to DIV 9.…”
Section: Resultsmentioning
confidence: 99%
“…As we speculated, BPA exposure significantly decreased the phosphorylation of mTOR and methylation level of PP2A, suggesting the adverse effects of BPA on insulin signaling pathway. The increases in the activities of GSK-3α and β are responsible for APP generation and the hyper-phosphorylation of tau, respectively 37 ; thus, these findings prompted us to infer that BPA exposure results in the enhancement of APP and p-tau expression. As speculated, the APP and p-tau expressions were substantially elevated after BPA exposure in SY5Y cells, and these effects were confirmed in another cell line, PC-12, which suggests that BPA affects APP and p-tau generation.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that TDP reduction is a significant biomarker for AD diagnosis [10]. The reduction of brain glucose metabolism and its possible pathogenic indicator, TDP reduction, implicate multiple pathogenic pathways in AD, including oxidative stress [11], neuroinflammation [12], and enhanced activity of glycogen synthase kinase-3 [13] and b-secretase [14]. Therefore, we hypothesized that disruption of thiamine metabolism directly contributes to AD pathogenesis by perturbing glucose utilization and by activating multiple pathophysiological cascades in the brain [15].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%